Effects of Feeding a Fermented Product on the Faecal Microflora and Egg Composition in Laying Hens - Law, Elizabeth Fang Lin (2006)
The thesis studied the characteristics of a fermented product (FP) and the effects of the FP on layers. Two experiments were conducted to achieve the objectives above. Experiment I (Chapter IV) was conducted to evaluate the composition and consistency of the finished fermented product (FP). The nutritive value and chemical compositions of the product were evaluated after the process of fermentation. In parallel, microbiological analyses, including lactic acid bacteria (LAB) and Enterobacteriaceae counts were also performed. The fermentation process was repeated three times under the same running conditions and using the same amounts of raw materials. The physical, chemical and microbiological properties of FP obtained in this study showed that FP had consistent chemical and microbiological characteristics. The presence of essential fatty acids (linoleic acid 24%, linolenic acid 1.1%, eicosapentaenoic acid 3.6%, docosapentaenoic acid 0.7%, docosahexaenoic acid 2.0%) and a lime-flavored aroma represent additional value-added attributes to the product. Experiment II (Chapter V) was carried out to investigate the effects of feeding FP to layers (Babcock B380) on faecal microflora, essential fatty acid and cholesterol levels in eggs and plasma. A total of 96, 13-week-old Babcock B380 pullets were used in this study. They were randomly assigned to four numerically equal groups with eight replicates per treatments, three birds per replicates. All the birds were housed in individual cages. Diet I (Cont), had no FP, Diet II (FP3) contained 3% (w/w) FP (30g FP/kg diet), Diet III (FP6) contained 6% (w/w) FP (60g FP/kg diet) and Diet IV (FP9) contained 9% (w/w) FP (90g FP/kg diet). The study lasted 16 weeks inclusive of two weeks of adjustment period and a 14-week experimental period. Weekly feed intake and egg production were recorded. Fresh faecal droppings were collected immediately and cultured for LAB and Enterobacteriaceae and pH and VFA production were also measured. Blood plasma cholesterol and fatty acid profiles were assayed at the end of the experiment. Results obtained from this study showed that FP reduced (P<0.05) the faecal Enterobacteriaceae and faecal pH. Higher (P<0.05) counts of faecal LAB in layers fed with FP were observed. However, FP did not enhance (P>0.05) the egg production and egg mass but (P<0.05) decreased the egg weight slightly. Feed intake and feed conversion ratio (FCR, feed intake/egg mass) were not affected (P>0.05). However, egg yolk cholesterol and plasma cholesterol concentrations were reduced (P<0.05) in the FP fed laying hens compared to the control laying hens. The n-6: n-3 ratio in the egg yolk (control=7.9, FP9=6.1) and plasma (control=10.46, FP9=6.54) from the FP fed laying hens were decreased compared to the control laying hens. Moreover, FP was able to increase (P<0.05) the polyunsaturated fatty acid (PUFA): saturated fatty acid (SFA) ratio, total n-3 PUFA and DHA concentrations in egg yolk and plasma. In summary, the results of the dietary manipulation demonstrated the effectiveness of FP in shifting the microflora composition of the avian GIT towards a beneficial balance. In addition, it has the ability to increase the unsaturated fatty acid (UFA) content to a more healthy proportion in eggs.